Always at the forefront of microwave electronics (on the occasion of the 50th anniversary of the "Saturn" Research Institute) - GlushechenkoE. М.; Chmil, V. M. (Technology and design in electronic equipment, 2018)
The article is devoted to the scientific and production enterprise "Saturn" - from the moment of creation to the present day. The decisive stages of its development and the scientific and technical results achieved by the team during the 50-year history of the enterprise are described.